Media Promosi Produk UMKM dengan Menggunakan EPIC Model - Ernestivita, Gesty; Subagyo (Universitas Nusantara PGRI Kediri, 2020)
MSMEs must be able to grow and develop in the era of global competition. The growth and development of MSME are shown by increasing sales volume and profitability. One of strategy to increase sales volume is promoting through social media, one of them is Instagram. This study aims to measure the effectiveness of using Instagram as a medium for promoting MSME products using the EPIC model. The study was conducted on 100 active Instagram owners who follow SMEs that promote their products through Instagram. Based on the EPIC Model, the most effective dimension is communication and it is included in a very effective scale range with a mean score of 4.14.